2008
DOI: 10.1177/1352458507088105
|View full text |Cite
|
Sign up to set email alerts
|

Soluble receptor for advanced glycation end products in multiple sclerosis: A potential marker of disease severity

Abstract: The significant reduction of sRAGE in MS patients relative to healthy controls supports the potential role for RAGE axis in MS clinical pathology. Lower levels of sRAGE may be associated with enhanced inflammatory responses. Based on these observations, further investigations into the role of sRAGE in MS clinical pathology is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…In addition, lower levels of serum sRAGE have been detected in several chronic inflammatory diseases, for example multiple sclerosis (MS), primary Sjogren's syndrome, and rheumatoid arthritis (RA). [29,30] To date, only two studies have investigated the serum sRAGE levels in SLE patients, and they reported conf licting results. [31,32] However, experimental animal models have provided encouraging results about the therapeutic role of sRAGE.…”
mentioning
confidence: 99%
“…In addition, lower levels of serum sRAGE have been detected in several chronic inflammatory diseases, for example multiple sclerosis (MS), primary Sjogren's syndrome, and rheumatoid arthritis (RA). [29,30] To date, only two studies have investigated the serum sRAGE levels in SLE patients, and they reported conf licting results. [31,32] However, experimental animal models have provided encouraging results about the therapeutic role of sRAGE.…”
mentioning
confidence: 99%
“…They also detected a relationship between sRAGE and EDSS as well as sRAGE and the rate of clinical relapse in MS patients [18]. The population of patients recruited in the current study was remarkably different from those in the Sternberg et al study, who included 31 RRMS and six secondary progressive (SP) MS patients.…”
Section: Discussionmentioning
confidence: 70%
“…This differs from our homogenized patient population consisting of 50 RRMS patients. More importantly, Sternberg et al enrolled patients who declined to take any Food and Drug Administration approved MS disease-modifying drugs (IFN-β, glatiramer acetate and natalizumab) [18], which could explain the discrepancies between our results and theirs.…”
Section: Discussionmentioning
confidence: 79%
“…With respect to sRAGE, akin to other inflammatory neurodegenerative syndromes discussed above, MS patients display lower serum levels of sRAGE relative to control patients and this decreased sRAGE inversely correlates with disease progression [108]. In addition, RAGE ligands are also increased in active MS lesions, as observed by immunohistochemistry.…”
Section: Multiple Sclerosis and Experimental Autoimmune Encephalopathmentioning
confidence: 90%
“…In addition, RAGE ligands are also increased in active MS lesions, as observed by immunohistochemistry. Further, AGER mRNA and RAGE ligand protein concentrations were increased in serum, CSF, and mononuclear cells in both niches during MS [108][109][110][111][112]. Interestingly, patients treated with disease-modifying drugs display a prominent reduction of serum HMGB1 when compared to untreated MS patients, which correlated to a better disease prognosis [111].…”
Section: Multiple Sclerosis and Experimental Autoimmune Encephalopathmentioning
confidence: 99%